Effect of β-cell secretory status and insulin resistance on the glycemic status of newly diagnosed youth-onset phenotypic type 2 diabetes mellitus: β-cell secretory status and insulin resistance in youth-onset DM (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Youth-onset phenotypic type 2 diabetes mellitus (T2DM) often presents with high plasma glucose and hemoglobin A1c (HbA1c).Objective: To assess the relationship of β-cell secretory status and insulin resistance (IR) with plasma glucose and HbA1c at diagnosis in phenotypic T2DM of young.Methods: This cross-sectional study enrolled 72 newly-diagnosed youth-onset phenotypically T2DM patients [age range 19-29, median 27, inter-quartile range (IQR) 24-29 years; 40 (55.6%) female] to see insulin secretory status by fasting C-peptide and insulin resistance by visceral adiposity index (VAI) along with serum triglyceride/high-density lipoprotein cholesterol (TG/HDL-C) ratio. C-peptide was measured by chemiluminescence immunoassay.Result: Median fasting plasma glucose (FPG), 2h plasma glucose (2h-PG) and HbA1c of the participants were 10.8 (IQR 7.1-16.3) mmol/L, 18.0 (IQR 13.1-24.3) mmol/L, and 8.7% (IQR 6.7-11.0) respectively. All glycemic values inversely correlated with fasting C-peptide (FPG: ρ =-0.48, p